Lassa Fever 2016 Outbreak in Plateau State, Nigeria—The Changing Epidemiology and Clinical Presentation - Shehu, Nathan Y.; Gomerep, Simji S.; Isa, Samson E.; Iraoyah, Kelly O.; Mafuka, Johnson; Bitrus, Nandom; Dachom, Matthias C.; Ogwuche, John E.; Onukak, Asukwo E.; Onyedibe, Kenneth I.; Ogbaini-Emovon, Ephraim; Egah, Daniel Z.; et al. (Frontiers in Public Health, 2018)
Lassa fever (LF) outbreaks in Nigeria mostly occur in rural areas and during the dry season, peaking between December through February. Fever is a cardinal presenting feature among the myriad manifestations of LF. Thirty four patients with clinical diagnosis of LF were analyzed. However, only 11 (32%) LASV infections were confirmed by RT-PCR. The 2016 LF outbreak showed a preferential urban occurrence and a high case fatality. Fever (≥38C ) was not detected in over a fourth of the patients at the time of examination. Bleeding diathesis was the most common presentation while abdominal pain and headache were present in more than half of the confirmed cases. Changes in the geographical distribution and clinical presentation may have implications for disease control efforts and the risk of transmission, both locally and internationally. In order to guide interventions, public health authorities should be aware that the epidemic patterns may be changing.